The role of parents and teachers in changing adolescents' perfectionism: A short-term longitudinal study. (1st September 2018) - Domocus, Iulia M.; Damian, Lavinia E.
Abstract: Although the important role of parents and teachers in the development of adolescent perfectionism is acknowledged, only few longitudinal studies have investigated this topic. Using a short-term longitudinal design with two waves spaced three months apart and a sample of adolescents, this study represents a first longitudinal investigation of parents and teachers as both risk and protective factors in perfectionism change. Results showed that perceived parental pressure predicted longitudinal increases in perfectionistic concerns and perceived anxious rearing predicted increases in socially prescribed perfectionism. Also, teacher support predicted longitudinal decreases in self-oriented perfectionism and in perfectionistic concerns. Implications of these findings for both research and practice are discussed. Highlights: Parents' and teachers' roles in changing adolescents' perfectionism were studied. Parental pressure predicted increases in perfectionistic concerns. Anxious rearing predicted increases in socially-prescribed perfectionism. Teacher support predicted decreases in self-oriented perfectionism. Teacher support predicted decreases in perfectionistic concerns.